A Typology of Crowd Configurations Based on Crowd Attributes and Their Impacts on Crowdsourcing Outcomes - Hee Rui He (IEEE Access, 2022)
Crowdsourcing, as a crowd-centered approach, is becoming increasingly popular for organizations to conduct outsourcing, research and development (R&D), and marketing. The effectiveness of a crowdsourcing initiative, as manifested in specific outcomes, depends significantly on the salient characteristics of the configured crowd. This study aims to investigate which business purposes necessitate which crowds with which characteristics. Contributions of this study include: 1) introducing and defining three crowd attributes to depict the salient characteristics of a crowd, and 2) proposing a typology of eight crowd configurations by combining high or low levels of the three crowd attributes and examining each crowd configuration to highlight the relationships between crowd attributes and crowdsourcing outcomes. Eight mini cases corresponding to the eight crowd configurations are presented to illustrate how crowd configurations were implemented in real-life situations. The theoretical and practical implications are discussed respectively.